2020
DOI: 10.1016/j.chiabu.2020.104715
|View full text |Cite
|
Sign up to set email alerts
|

‘When will I be free’: Lessons from COVID-19 for Child Protection in South Africa

Abstract: Background COVID-19 has highlighted and amplified structural inequalities; drawing attention to issues of racism, poverty, xenophobia as well as arguably ineffective government policies and procedures. In South Africa, the pandemic and the resultant national lockdown has highlighted the shortcomings in the protection and care of children. Children in alternative care are particularly at risk as a result of disrupted and uncoordinated service delivery. Objective The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 38 publications
1
46
0
3
Order By: Relevance
“…Anthropologist Bronislaw Malinowski (2018) noted that historically death was considered as much more than the departure of a family member, and that the ceremonial rituals addressed the fears, sadness, and disheartenment faced by the family, serving to unite and strengthen them through their time of grief. Reports of families’ inability to grieve in the usual, unhurried, ceremonial manner have been frequent due to COVID-19 ( Haffejee, 2020 ).…”
Section: Healing Grief and Rituals In The Pandemicmentioning
confidence: 99%
“…Anthropologist Bronislaw Malinowski (2018) noted that historically death was considered as much more than the departure of a family member, and that the ceremonial rituals addressed the fears, sadness, and disheartenment faced by the family, serving to unite and strengthen them through their time of grief. Reports of families’ inability to grieve in the usual, unhurried, ceremonial manner have been frequent due to COVID-19 ( Haffejee, 2020 ).…”
Section: Healing Grief and Rituals In The Pandemicmentioning
confidence: 99%
“…The restrictions introduced as a result of the COVID-19 pandemic have posed an added difficulty for children in care given their home situation and needs, placing them in an especially vulnerable position ( CFECFW, 2020 ; OECD, 2020 ). In this regard, one of the most important points to highlight is that contacts with the biological family were interrupted or limited and face-to-face visits replaced by online visits, causing an increase in stress for the children, their biological families and caregivers ( Haffejee & Levine, 2020 ; Neil, Copson, & Sorensen, 2020 ) and hindering reunification processes or stopping them altogether ( Callejas, Davidson, & Ismajli, 2020 ; Singer & Brodzinsky, 2020 ). Specifically in Catalonia, where this study took place, face-to-face visits were not resumed until mid-May and were subject to highly restrictive conditions (no overnight stays, only with parents, and accompanied by assigned caregivers or practitioners) ( DGAIA, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, in a very different context, the results of a qualitative study conducted in 32 children in residential care, showed the diversity of personal experiences among children in the same children's home and the complexity of studying the impact of lockdown in this context. The children's emotions ranged from well-being to anger and frustration and they had ambivalent feelings that oscillated between feeling safe in the children's home and, at the same time, being affected by reduced contact with their biological family and concerned about their health ( Haffejee & Levine, 2020 ). Finally, a recent study including representatives from 67 non-governmental organisations in 14 different countries pointed out that, as a result of the COVID-19 outbreak, children in residential care were being returned more hastily to their biological families without receiving appropriate preparation and counselling beforehand, exposing these children to greater risk ( Wilke, Howard, & Goldman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the Covid-19 pandemic phenomenon gave rise to many new elements in early childhood research, such as economic, social, and political issues that turned out to be hidden behind early childhood issues. Reveal new shortcomings that have yet to emerge, including enlarging the dimensions of inequality [8] which is seen in public health, social structures, and systems [9] around children.…”
Section: Introductionmentioning
confidence: 99%